The repetitive DNA sequence landscape and DNA methylation in chromosomes of an apomictic tropical forage grass, Cenchrus ciliaris - Rathore, Priyanka; Schwarzacher, Trude; Heslop-Harrison, J. S.; Bhat, Vishnu; Tomaszewska, Paulina (Frontiers in Plant Science, 2022)
Cenchrus ciliaris is an apomictic, allotetraploid pasture grass widely distributed in tropical and subtropical regions of Africa and Asia. In this work, we aim to investigate the genomic organization and characterize the nature of repetitive DNA sequences in this species. Because of the apomictic propagation, various aneuploid genotypes are found and we analysed here a 2n=4×+3=39 accession. The physical mapping of Ty1-copia and Ty3-gypsy retroelements through fluorescence in situ hybridization with global assessment of 5-methylcytosine DNA methylation through immunostaining revealed the genome-wide distribution pattern of retroelements and their association with DNA methylation. About a third of Ty1-copia sites overlapped or spanned centromeric DAPI positive heterochromatin, while the centromeric regions and arms of some chromosomes were labeled with Ty3-gypsy. Most of the retroelement sites overlapped with 5-methycytosine signals, except some Ty3-gypsy on the arms of chromosomes which did not overlap with anti-5-mC signals. Universal retrotransposon probes did not distinguish genomes of C. ciliaris showing signals in pericentromeric regions of all 39 chromosomes, unlike highly abundant repetitive DNA motifs found in survey genome sequences of C. ciliaris using graph-based clustering. Probes developed from RepeatExplorer clusters gave strong signals mostly in pericentromeric regions of about half of the chromosomes, and we suggested that they differentiate the two ancestral genomes in the allotetraploid C. ciliaris likely having different repeat sequence variants amplified before the genome came together in the tetraploid.